Boring FB Page? What’s Wrong? - Mat Yamin, Fadhilah; Wan Ishak, Wan Hussain; Abu Bakar, Siti Zakiah (2022)
Digital platforms are gaining ground now along with the advancement of technology. However, this technology needs to be utilized in the best way to get satisfactory results. Therefore, this teaching case discuss a micro SME entrepreneur, namely Mr. A who has used social media ie FB page for product marketing. However, he is still not satisfied with the strategy he has implemented and needs your advice by checking his FB page and giving suitable suggestions to boost his product promotion.